IMPLEMENTASI ALGORITMA C.45 DALAM PREDIKSI PENYAKIT KANKER - Warid Yunus; Abd Rahmat Karim Haba (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
Cervical cancer detection has not been carried out stably because the patient came to the AlieSaboe Hospital where the patient's condition had entered an advanced stage. So that the results of treatment are very low, it would be better if the treatment is carried out at an earlier stage. So that the death rate of patients is expected to decrease. Factors that influence patients arriving late with reasons of embarrassment, fear of knowing the results of the detection of their disease. The purpose of this study was to obtain the C.45 Algorithm Model in predicting cervical cancer patients. The results achieved by this study are to obtain prediction results using the C.45 algorithm and have an accuracy of 70.37% as measured using the Confusion Matrix on Rapid Miner tools.